Organizational Behavior Management (OBM) impact: Citation analysis in Business journals - Soares, Pedro Felipe dos Reis; Santos, Analine Lopes dos; Falcão, Gabrieli Rodrigues; Souza, Gilvandro Figueiredo (Perspectivas em Análise do Comportamento, 2025)
Organizational Behavior Management is a subdomain of Behavior Analysis that focuses on research and application related to human behavior in organizational environment. Bibliometric surveys have shown that the area is growing in national Behavior Analysis. Business is a science with potential for mutual influence with Behavior Analysis through Organizational Behavior Management, and a bibliometric examination of the approximation between these disciplines has not yet been carried out. In order to gauge the influence of Organizational Behavior Management on knowledge production in Business, citations to studies from the Journal of Organizational Behavior Management were examined in articles from the main Business journals between 2014 and 2023. Citations to studies in the Journal of Applied Psychology were analyzed as a comparison. Nine articles with citations to Journal of Organizational Behavior Management publications were found, compared to 402 with citations to Journal of Applied Psychology. Most of the citations to Journal of Organizational Behavior Management papers were to the same article in Consumer Behavior/Marketing. The quality of these citations ranged from “Intermediate” to “Central”. In the high-quality academic sphere of national Business, the Journal of Organizational Management articles were cited very little. Possibilities for broadening the search in new surveys are discussed, as well strategies for effective communication with the field of Business.